Peran Manajemen Proyek Dalam Pengembangan Berbasis Web - Divanca Salma Fadillah; Yuni Sugiarti (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
Carrying out a development project definitely requires more effort and careful planning in all technical and administrative aspects so that the project can be carried out properly. The rate of failure in the project proved to be very high, seen from the obstacles and obstacles in the development project. This must be addressed in an appropriate manner. Therefore we need an appropriate project management technique, where project management is a collection of strategies in the implementation of skills, knowledge, and management techniques in planning, organizing, and developing to improve efficiency and effectiveness. In the information system development project itself there are several methods and platforms. Some of the platforms commonly used in development projects are web-based, mobile, and desktop. This research was conducted to determine the importance of the role of project management in web-based development. The study uses the Systematic Literature Review (SLR) method by analyzing the data obtained based on relevant literature related to project management from 2017 to 2022. With the SLR method, several articles from journals can be easily reviewed and systematically identified.